Comparable Antifungal Activity of Binahong (Anredera cordifolia) Leaf and Stem Ethanol Extracts Against Colletotrichum gloeosporioides Isolated from Anthracnose-infected Curly Red Chili - Iis Rohayati; Nur Imaniati Sumantri; Junaidi; Megga Ratnasari Pikoli (Al-Kauniyah: Jurnal Biologi, 2026)
Colletotrichum gloeosporioides is one of the pathogens that causes anthracnose in curly red chili (Capsicum annuum L. var. Longum). Anthracnose in red chile is marked characterized by fruit damage and consequently reduced market value. Anredera cordifolia (binahong) contains various bioactive compounds with presumed antifungal activity. Most binahong studies focus on the leaves, whereas this study compared the antifungal activity ethanol extracts from the leaves and stems against Colletotrichum gloeosporioides isolated from anthracnose-infected curly red chili fruits. An experimental method was used by varying extract concentrations in the binahong stem and leaf treatment groups. Fungus from anthracnose-infected fruit was isolated, purified, and identified as Colletotrichum gloeosporioides. Binahong leaves and stems were extracted with 96% ethanol and tested in two sequential stages at various concentrations, both showing that the highest concentrations exhibited the greatest inhibitory activity with no significant difference between leaf and stem extracts (P >0.05). Therefore, the leaf and stem extracts of binahong have similar biofungicidal potential that increases proportionally with concentration, against Colletotrichum gloeosporioides from curly red chili fruit.